B1 repetitive sequence methylation enhances wound healing of second‑degree burns in rats. Issue 3 (2022) - MEEVASSANA‑, JIRAROCH; NACHAROENKUL, PANUPONG; WITITSUWANNAKUL, JADE; KITKUMTHORN, NAKARIN; HAMILL, KEVIN J.
No abstract available